GENDERED LANGUAGE IN ADVERTISING SLOGANS: A CRITICAL DISCOURSE STUDY - Isabella Garcia (International Journal of Literature and Language Studies, 2026)
This article analyzes how advertising slogans reproduce and challenge gendered meanings. The study responds to the problem that advertising language is short and memorable, but its compressed form often carries assumptions about gender, desire, authority, and social roles. Using critical discourse analysis focusing on lexical choice, address forms, presupposition, and implied audience, the article analyzes a purposive sample of print and online advertising slogans from beauty, technology, fashion, and household products. The findings indicate that many slogans continued to associate women with beauty and care while associating men with performance and control, although some recent slogans used empowerment vocabulary to contest older patterns. The article argues that slogan analysis reveals how small linguistic units participate in broader cultural debates about gender representation. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.